Contribution to work and management improvement in the Military Academy and the University of Defence - Andrejić, Marko D.; Andrejić, Ivana M.; Arsić, Slaviša N.; Ljubojević, Srđan D. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Robust and dynamic organizational changes that have been carried out in defense in recent years affected the field of higher education and scientific research related to defense . A creation of a new, integrated research and education system, harmonized with the national system, is underway. Such a system will be resilient and partly self-sustainingt and useful not only for the defense area, but also for the wider community. Introduction Higher education is a very important part of the strategy of power and the influence of a real defense system. Creativity as a basic resource produces innovations which can enhance and improve the defense system. Organizational changes in the country over the last decade did not miss its defence system, an important state function and the field of objective social reality. The most important change in the defense system has resulted in the formation of the UD. Approach to improving teaching and scientific work at the Military academy and the University of Defence Education should not be seen as a cost but as an investment, seriously prepared in the adequate organizational environment (Andrejić et al, 2011, pp.5-26). As a result , the improvement of the quality of education and research at the UD should be aligned with the long-term development concept of the defense system and the society as a whole, taking into account the technology of the process of education and training since fast, cheap and, at the same time, high- quality solutions in education are not known . It is possible to achieve a necessary flexibility in response to significant technological and organizational challenges by improving and developing new programs to meet the needs of practice . Institutional framework for the advancement of teaching and scientific work in the Military Academy and the University of Defence Before applying organizational measures and procedures aimed at improving the quality of education and research at the Military academy, it is necessary to know the relevant factors and preconditions of organizational changes . From the production-process point of view, it is necessary to reduce the range of products provided by theUD and to gradually specialize in certain products, in order to ensure internal and external competitiveness. In this regard, it is necessary to create conditions so that lecturers of methodological and theoretical academic general education courses at the UD are experts from relevant civilian universities while the UD and the Military Academy in particular should develop teaching and research human resources for scientific-professional and professional-applied science courses. The main activity and the purpose of the Military Academy should be clear to an objective and independent observer.from outside the Academy. Within the Military Academy, all functions and business processes should aim at quality higher education and research in the field of defense. In accordance with the requirements of time, a conceptual orientation and the nature of the University itself, the academic spirit and freedom must take precedence over professional aspects of education (performance of training centers and colleges of professional studies). At the same time, higher operating efficiency and effectiveness are necessary to reach strict criteria and requirements of the modern academic environment . Management of changes to improve the teaching and scientific work at the Military Academy and the University of Defence Change management involves coping with challenges that can be identified as: lack of creativity and value or cultural barriers; group solidarity, group thinking; conformity in relation to the previously accepted norms; structural divisions; distribution of authority; technology; philosophy of management; management style, etc. The man is the dominant factor of changes and good understanding of the nature of human behavior is a necessity and the measure of all actions taken. For detecting, understanding and overcoming the passivity of change (maintaining the "status quo "), it is necessary to choose adequate management staff. Conclusion The management and organization of the system can be improved by encouraging changes at the micro, meso and macro levels and by professional approach in the selection, training and development of managers. The University of Defence needs to be further developed and strengthened through the improvement of quality in the performance of primary activities, quality management and planning and the introduction of a labor - stimulating system. The comparative advantages on which it is possible to base the changes are: knowledge, experience and "know how" . The attitude towards one’s own future is reflected in the attitude towards creativity and knowledge as the most valuable resources, which can, to some extent, compensate for the lack of material resources - therefore, they need special attention.